Surgical treatment of a bilateral congenital tarsal hyperextension in two cats (Veterinary Science, 2017)
Two kittens were admitted with bilateral congenital tarsal abnormalities.We decided they should both undergo surgicaltreatment at an early age. Surgical treatment consisted in transarticularExternal Skeletal Fixation (ESF) for a period of 3 to 4weeks. Shortly after ESF removal both patients re-gained tarsalmobility, remaining stable with adequate functionality. One patienthad two coexisting developmental orthopedic pathologies
Keywords: cat; congenital; tarsal joint; surgery